Review of Design and Implementation of Automated Drugs Mixer - Hayder Ajmi Beshet; Ahmed Rashid Ajel; Aws Basil Hamed; Noaman Mohammad Noaman (Journal of Techniques)
Macromixing and drug control are becoming more essential in a wide range of chemical and biological applications. The efficacy of microfluidic macromixing devices, which are particularly beneficial to give an exact quantity of material at specified times, is greatly influenced by the infusion pump. The construction of a low-cost functional prototype of an infusion pump in the management of delivery rates that are variable and low in particular quantities is proposed in this study. The infusion pump may be seen working at various flow rates, proving that the device may be utilized to control the volume and rate of flow of chemical fluids in medical settings, in addition to microfluidic mixing investigations in specific and scientific studies, In general, the biomedical field.